PROTOTYPE OF CONTACTLESS PAYMENT SYSTEM WITH RFID AND BLOCKCHAIN TECHNOLOGY INTEGRATED WITH MOBILE APPLICATION - Jiustian, Danny; Yohannis, Alfa (Jurnal Teknik Informatika (Jutif), 2024)
The COVID-19 pandemic has led to a change in payment methods, with a shift towards cashless payments to avoid germs and viruses. Contactless payments, especially those using RFID technology, have become popular due to their convenience and no need to enter security codes. However, there is a risk of data manipulation in transaction records, leading to decreased trust and transparency. To solve this problem, this research develops an RFID contactless payment system connected with blockchain technology as the main goal of the research. Blockchain is known for its security and transparency, making it suitable for minimizing data manipulation that often occurs. This research will use the Sepolia Test Network of the Ethereum base network for development in terms of blockchain to serve as a security layer in this research. The Waterfall method will be used for application development, focusing on structured and linear stages such as requirements analysis, system design, implementation, testing, and maintenance. The application development process has shown positive results, with successful black box testing and the ability to track and validate transactions stored in the database and blockchain. This validation process is critical to ensure the integrity of transactions and detect any data manipulation.